2014
DOI: 10.11650/tjm.18.2014.1489
|View full text |Cite
|
Sign up to set email alerts
|

Total Scalar Curvature and Harmonic Curvature

Abstract: On a compact n-dimensional manifold, it has been conjectured that a critical point metric of the total scalar curvature, restricted to the space of metrics with constant scalar curvature of unit volume, will be Einstein. This conjecture was proposed in 1984 by Besse, but has yet to be proved. In this paper, we prove that if the manifold with the critical point metric has harmonic curvature, then it is isometric to a standard sphere.1991 Mathematics Subject Classification. 58E11, 53C25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…which appears similar to (8). An argument very similar to that used in the proof of Theorem 1.1 enables us to prove Theorem 1.3.…”
Section: Manifolds With Nontrivial Kernelsmentioning
confidence: 63%
See 1 more Smart Citation
“…which appears similar to (8). An argument very similar to that used in the proof of Theorem 1.1 enables us to prove Theorem 1.3.…”
Section: Manifolds With Nontrivial Kernelsmentioning
confidence: 63%
“…Lafontaine showed that the conjecture holds if a solution metric g is conformally flat and the kernel of s ′ * g is nontrivial, or ker s ′ * g = 0 [5]. Recently, Yun, Chang, and Hwang showed that the Besse conjecture is true for Riemannian manifolds with harmonic curvature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Barros and Ribeiro Jr [3] proved that the CPE conjecture is also true for half conformally flat. Another partial proof of the CPE conjecture was presented by Yun, Chang and Hwang [12]. They proved that if (g, λ) is a non-trivial solution of the CPE on an n-dimensional compact Riemannian manifold M and satisfies one of the following conditions (i) Ricci tensor of g is parallel (ii) g has harmonic curvature or (iii) g is conformally flat, then (M, g) is isometric to a standard sphere.…”
Section: Introductionmentioning
confidence: 99%
“…[18]). Let (g, f ) be a non-trivial solution of (1.8) on an n-dimensional compact manifold M , n ≥ 4.…”
mentioning
confidence: 99%
“…Note that the function α is defined only on the set M ∖ Crit(f ), where Crit(f ) is the set of all critical points of f . However, since α ≤ z , α can be extended to a C 0 function on the whole manifold M (for more details, see [18]). Therefore, when T = 0, it follows from (5.3) that…”
mentioning
confidence: 99%